THE INFLUENCE OF EDUCATION, EMPLOYMENT AND CARE FOR THE INDEPENDENCE OF CHILDREN - Latifah, Latifah; Wahyu, Wahyu; Metroyadi, Metroyadi (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
This study aims to analyze and describe the influence of education, level of parenting, and occupation on children?s independence.  A total of 212 parents and children were used to carry out this research using the simple random sampling technique. The data obtained were examined and utilized to test hypotheses using the path analysis. Data processing was carried out using IBM SPSS version 24.0 computer program. The results consists of the following points: There are direct influences: (1) Level of parental education about childcare (2) Parents 'work on childcare (3) Parent's level of education about children's independence (4) Parents' work on children's independence ( 5) Parenting style for child stagnation. While the no indirect influence comprises of the following (6) The level of parental education on children's independence through parenting (7) Parents' work on children's independence through parenting. However, there were no indirect influences.